GnRH agonist-only trigger, compared to dual trigger, reduces oocyte retrieval rate in high responders without affecting cumulative live birth rate - Wang, Yu; Yi, Yu-Chiao; Guu, Hwa-Fen; Chen, Ya-Fang; Kung, Hsiao-Fan; Chang, Jui-Chun; Chen, Li-Yu; Chuan, Shih-Ting; Chen, Ming-Jer (Frontiers in Endocrinology, 2024)
Introduction This study compared, in high responders undergoing IVF treatment, GnRH agonist-only trigger and dual trigger on oocyte retrieval rate and cumulative live birth rate (LBR). The aim was to determine if the GnRH agonist-only triggers had provided outcomes comparable to dual trigger, while minimizing the risk of ovarian hyperstimulation syndrome (OHSS). Materials and methods A retrospective, matched case-control study was conducted at Taichung Veterans General Hospital, Taiwan, including women who underwent IVF/ICSI between January 1, 2014, and December 31, 2022. Inclusion criteria were: GnRH antagonist protocol and estrogen level >3,000 pg/ml on trigger day. Exclusion criteria were: immune/metabolic diseases, donated oocytes, and mixed stimulation cycles. Propensity score matching was applied to balance age, AMH level, and oocyte number between the GnRH agonist-only and dual trigger groups. Outcomes were analyzed for patients who had complete treatment cycles, focusing on oocyte retrieval rate and cumulative LBR. Results We analyzed 116 cycles in the agonist-only group, and 232 cycles in the dual trigger group. No inter-group difference was found in their age, BMI, and AMH levels. The dual trigger group had a higher oocyte retrieval rate (93% vs. 80%; p <0.05), while fertilization rates, blastocyst formation rates, and cumulative LBR were comparable. Notably, no OHSS cases had been reported in the GnRH agonist-only group, compared with 7 cases in the dual trigger group. Conclusion GnRH agonist-only triggers resulted in a lower oocyte retrieval rate compared to dual triggers but did not significantly affect cumulative LBR in high responders. This approach effectively reduces OHSS risk without compromising pregnancy outcomes, making it a preferable option in freeze-all strategies, despite a longer oocyte pick-up duration and a medium cost. GnRH agonist-only trigger, however, may not be suitable for fresh embryo transfers or patients with low serum LH levels on trigger day.